America`s Cup sailing: Effect of standing arm-cranking ("grinding") direction on muscle activity, kinematics, and torque application - Pearson, S. N.; Hume, P. A.; Cronin, J.; Slyfield, D. (Sports, 2016)
Grinding is a key physical element in America`s Cup sailing. This study aimed to describe kinematics and muscle activation patterns in relation to torque applied in forward and backward grinding. Ten male America`s Cup sailors (33.6 5.7 years, 97.9 13.4 kg, 186.6 7.4 cm) completed forward and backward grinding on a customised grinding ergometer. In forward grinding peak torque (77 Nm) occurred at 95 (0 = crank vertically up) on the downward section of the rotation at the end of shoulder flexion and elbow extension. Backward grinding torque peaked at 35 (69 Nm) following the pull action (shoulder extension, elbow flexion) across the top of the rotation. During forward grinding, relatively high levels of torque (>50 Nm) were maintained through the majority (72%) of the cycle, compared to 47% for backward grinding, with sections of low torque corresponding with low numbers of active muscles. Variation in torque was negatively associated with forward grinding performance (r = 0.60; 90% CI 0.88 to 0.02), but positively associated with backward performance (r = 0.48; CI = 0.15 to 0.83). Magnitude and distribution of torque generation differed according to grinding direction and presents an argument for divergent training methods to improve forward and backward grinding performance.